SOSIALISASI KURIKULUM MERDEKA BELAJAR SEBAGAI REFORMASI PENDIDIKAN MASA KINI - Yanti, Febri; Silalahi, Mastiur Verawaty; Situmorang, Masni Veronika (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
Every school is currently preparing school teachers to understand and study the independent curriculum so that every teacher understands and teaches according to the curriculum that has been determined by the government. For this reason, the school invited lecturers as speakers to socialize what an independent curriculum is with the topic presented